Analysis of Update Mapping in Science Learning Media Research: Bibliometric Analysis Based on Google Scholar Data - Sigit Subagja; Didit Ardianto; Bibin Rubini (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
This article presents a review of bibliometric analysis on the topic of science learning media research. The aim of this research is to identify relevant research and the latest research on the research topic being analyzed. The method used in this research is descriptive quantitative with bibliometric data approach. Research data collection is carried out on the Google Scholar page with the help of Publish or Perish (PoP) software using the keyword